OP0305-HPR Quality Indicators for Physiotherapy Management in Hip and Knee Osteoarthritis and Rheumatoid Arthritis; Development and Measurability. (9th June 2015) - Peter, W.F.; Hurkmans, E.J.; van der Wees, P.J.; Hendriks, E.J.; van Bodegom-Vos, L.; Vliet Vlieland, T.P.
Abstract : Background: Physiotherapy (PT) is recommended in several guidelines on the management of hip and knee osteoarthritis (HKOA) and rheumatoid arthritis (RA). Currently, no specific quality indicators (QI) for PT in patients with HKOA and RA are available. Objectives: To develop QI for the PT management of patients with HKOA and RA, and to make them measurable. Methods: The first concept QI were derived from the recommendations included in two Dutch PT evidence based practice guidelines for HKOA and RA using a modified RAND/UCLA Delphi method in accordance with the requirements of the AGREE II HCQI tool.[1] Two multidisciplinary expert groups (HKOA and RA) of 19 persons were composed containing patients; a patient representative from the Dutch Arthritis Association; PTs; general practitioners; rheumatologists; an orthopaedic surgeon; a rehabilitation physician; an occupational therapist; and researchers. Using Delphi rounds, each expert group could suggest other topics for the set of QI, and then scored all topics with respect to relevance (score range 0 = not at all relevant to 9 = extremely relevant) and feasibility of measuring. Potential topics were selected if a score of >6 was obtained by >75% of the experts regarding aspects representing good quality of PT care. QI with scores 5 or 6 were again entered into a Delphi round and selected for the final set based on comments of the expert arguments. Selected QI were then combined and reformulated by the project group. Finally, for each QI a numerator and denominator was formulated in order to quantify the indicator for usage in daily clinical practice to measure and evaluate quality of PT care. Results: According the predefined rules in the two Delphi rounds 2 final sets with 17 QI for HKOA and RA each, were composed, both containing 16 process indicators (regarding initial assessment, treatment and evaluation) and one outcome indicator. To quantify each QI the numerator was formulated as follows (example): " The number of patients with hip and/or knee osteoarthritis that was (again) treated the past 12 months and in which, for hip and knee osteoarthritis specific, red flags were evaluated ". Subsequently the denominator was formulated as follows: " The total number of patients with hip and/or knee osteoarthritis that was (again) treated the past 12 months ". The resulting proportion of each QI is a measure of quality of PT care. Conclusions: Two valid and acceptable sets of 17 QI for PT management in HKOA and RA were developed and made suitable to measure and evaluate quality of PT care in daily clinical practice. Future research should focus on feasibility, reliability and sensitivity to change in daily PT practice and methods for collecting data. References: http://www.agreetrust.org/resource-centre/agree-ii/ Disclosure of Interest: None declared